An empirical investigation of the mitigating effect of debt on overinvestment as shareholder rights vary - Chung, Chune Young; Kim, Daejin; Lee, Junyoup (Bulletin of Economic Research, 2024)
In this study, we investigate the relationship between debt governance and overinvestment. We use net cash flows to debtholders as a proxy for debt governance and find that an increase in these cash flows mitigates firms' overinvestment. We also show that free cash flows lead cash-rich and cash-poor firms to overinvest but that debt governance attenuates this problem. Finally, we find that the mitigating effect of net cash flows to debtholders on overinvestment is highly pronounced in firms with poor governance. These findings suggest that net cash flows to debtholders are particularly effective when shareholder governance is weak. We conclude that cash flows to debtholders can effectively prevent overinvestment and reduce the agency costs of free cash flows.
Keywords: agency problem; free cash flow; optimal cash level; overinvestment; past debt creation